A Pt-based water-gas shift reaction catalyst and its preparation method and application

By introducing alkali metal borate into the water-gas transformation catalyst and modifying the Pt-based catalyst, the problems of insufficient low-temperature reaction activity and poor stability of the catalyst are solved, and the catalytic effect with high activity and good stability is achieved. It is suitable for the rapid start-up and repeated start-stop applications of fuel cell systems.

CN116212863BActive Publication Date: 2025-04-08DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202111468057.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-03
Publication Date
2025-04-08
Estimated Expiration
2041-12-03

AI Technical Summary

Technical Problem

The existing water-gas conversion catalysts have insufficient reactivity in the low-temperature zone, poor long-term operation and start-stop stability, and require reduction treatment, which limits their application in fuel cell systems.

Method used

The Pt-based water gas conversion reaction catalyst modified by alkali metal borate is used to load Pt, alkali metal borate and support through the impregnation method to simplify the preparation process and adapt to a fast start and repeated start-stop environment without pre-reduction.

Benefits of technology

It significantly improves the activity and stability of the catalyst, can maintain high reactivity at low temperatures, has good long-term operation and start-stop stability, and is suitable for fast-start fuel cell systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116212863B_ABST
    Figure CN116212863B_ABST
Patent Text Reader

Abstract

The present invention relates to a Pt-based water-gas shift reaction catalyst, a preparation method and an application. The water-gas shift reaction catalyst provided by the present invention is composed of Pt / alkali metal borate / carrier, the active component of the catalyst is Pt, and the Pt content is 0.5% to 10% of the total mass of the catalyst; the alkali metal borate content in the catalyst is 1% to 40% of the total mass of the catalyst; the carrier is one or a combination of two or more of CeO2, Al2O3, ZrO2, TiO2 and SiO2. Alkali metal borate and active component Pt are introduced by an impregnation method. The present invention improves the ability of the catalyst to activate water and inhibits the formation of carbonate species through the introduction of alkali metal borate, so that the catalyst provided by the present invention has high activity and start-stop stability in the water-gas shift reaction; at the same time, the catalyst provided by the present invention does not need to be reduced before the reaction, and is suitable for a fuel cell system with rapid start-up and repeated start-stop, and has a wide range of application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new energy, and in particular relates to a Pt-based water-gas shift reaction catalyst, a preparation method and an application thereof. Background Art

[0002] At present, the over-exploitation of fossil fuels has led people to look for alternative products to traditional fuels, among which hydrogen and alcohols (methanol, ethanol) have the greatest potential. Among the development and utilization of many new energy sources, hydrogen energy has also received widespread attention for its unique development potential and advantages. With the development of the hydrogen energy economy, hydrogen fuel cells have become an important new energy application platform. However, whether fossil fuels or ethanol and methanol are used as raw materials, the reforming process produces a large amount of CO while producing H2. CO has a strong toxic effect on fuel cell electrocatalysts, so fuel cells have strict restrictions on the CO content in hydrogen raw materials, which is generally less than 10ppm. The water-gas shift reaction is an effective method to eliminate CO in the reformed gas. It converts CO into CO2 and H2 through the reaction of CO and water, which can not only reduce the content of CO, but also effectively increase the content of H2. Therefore, the water-gas shift catalyst plays a very important role in the fuel cell system and is the key to the commercialization of hydrogen-carrying fuel cells.

[0003] Industrial water-gas shift reaction is usually carried out in a fixed bed reactor equipped with Fe3O4-Cr2O3 or Cu / ZnO / Al2O3 catalyst. Fe3O4-Cr2O3 is used for high-temperature water-gas shift reaction, with an operating temperature of 350-400°C, to achieve a faster conversion of CO, but due to the limitation of thermodynamic equilibrium, the CO concentration cannot be reduced to a very low level; Cu / ZnO / Al2O3 is used for low-temperature water-gas shift reaction, with an operating temperature of 200-250°C, to further reduce the CO concentration. The advantage of Co-Mo sulfur-resistant shift catalyst is its strong sulfur resistance and anti-poisoning performance. The biggest disadvantage is that it has high activity only in the sulfurized state, and a cumbersome sulfurization process is required before use.

[0004] Since traditional water-gas shift catalysts have many limitations in fuel cell applications, the development of water-gas shift catalysts for fuel cell hydrogen production systems has attracted great attention. For the removal of CO from fuel cell H2, the performance of water-gas shift catalysts must meet the following points: (1) high reactivity in the low temperature region (below 300°C) to ensure that the outlet CO concentration is sufficiently low; (2) stability in a stable state and a high number of cycles, that is, in the process of continuous heating-cooling; (3) high mechanical strength at high temperatures and impact conditions; (4) no side reactions occur, especially methanation reactions that consume a lot of hydrogen. At present, precious metal (such as Pt, Au, etc.) catalysts supported on various oxide carriers (such as CeO2, ZrO2, TiO2, etc.) are the water-gas shift catalysts that are more suitable for use in fuel cell systems and are currently being studied more.

[0005] Chinese patent CN103586023A discloses a Pt-based catalyst for water-gas shift reaction and a preparation method thereof. Specifically, a Pt / CeO2 catalyst with different morphologies is synthesized by a hydrothermal method. The catalyst prepared by the method performs a water-gas shift reaction in a typical reformed gas and has high activity and stability.

[0006] Chinese patent CN111139108A ​​discloses a water-gas shift reaction catalyst with a structural formula of Pt / @ZrO2 / SBA-15, which includes a composite carrier formed by dispersing ZrO2 on SBA-15 and an active metal Pt loaded on the composite carrier, wherein the content of ZrO2 in the composite carrier is 8.5-11wt%, and the content of active metal Pt in the catalyst is 1-2wt%. Compared with the conventional CO water-gas shift catalyst, the catalyst of the invention has higher catalytic activity and synergistic catalytic effect, and can obtain higher catalytic efficiency at relatively low temperature.

[0007] Chinese patent CN101199929 discloses a macroporous Pt / CeO2 catalyst for water-gas shift reaction and its preparation method, the catalyst uses three-dimensional ordered macroporous oxide CeO2 as a carrier, Pt as an active ingredient, and the mass content is 0.5-5% of the mass of the catalyst. The preparation method includes: using polystyrene as a template and Ce solution as a precursor solution, repeatedly impregnating the template, and programmed temperature calcination to obtain a three-dimensional ordered macroporous oxide CeO2; impregnating the macroporous CeO2 in H2PtCl6 solution, drying and calcining to obtain a three-dimensional ordered macroporous Pt / CeO2 catalyst. The invention has a simple and easy preparation process, and the obtained catalyst has the characteristics of high activity, good selectivity and good stability for water-gas shift reaction.

[0008] From the reported literature, although Pt / reducible oxide catalysts have high activity, whether it is Pt / TiO2 (Applied Catalysis A: General, 2008, 338, 66-71), Pt / CeO2 (Applied Catalysis B: Environmental, 2005, 56, 69-75) catalysts, or Pt / CeO2-ZrO2 (Applied Catalysis B: Environmental, 2006, 65, 135-141) catalysts, they all have the problem of insufficient low-temperature activity and poor catalyst stability. Maria Flytzani-Stephanopoulos et al. (Science, 2010, 346, 1498) found that the addition of alkali metals can significantly improve the low-temperature activity of Pt-based water-gas shift reaction catalysts, but the direct introduction of alkali metals makes the catalyst more likely to form carbonate species at low temperatures, and the catalyst activity decreases rapidly with the start-stop operation.

[0009] In summary, although the performance of Pt-based water-gas shift reaction catalysts has been greatly improved after years of research, there are still the following shortcomings: 1. The catalyst temperature activity is insufficient, resulting in the inability to further reduce the outlet CO concentration; 2. The long-term operation stability and start-stop stability of the reducible carrier-loaded precious metal water-gas shift catalyst need to be further improved. Summary of the invention

[0010] Based on the above research status, the present invention proposes an alkali metal borate modified Pt-based water-gas shift reaction catalyst, a preparation method and an application. In the catalyst provided by the present invention, the addition of alkali metal borate can significantly improve the catalyst activity, improve the long-term operation stability and start-stop stability of the catalyst, and does not require reduction before use. It is suitable for fast start-up and repeated start-stop fuel cell systems, and has broad application prospects.

[0011] To achieve the above object, the technical solution of the present invention is as follows:

[0012] The first aspect of the present invention provides a Pt-based water-gas shift reaction catalyst, characterized in that: the catalyst composition is Pt / alkali metal borate / carrier. The active component in the catalyst is Pt, and the Pt content is 0.5% to 10% of the total mass of the catalyst, preferably 0.8 to 8wt%, and more preferably 1-5wt%; the alkali metal borate in the catalyst includes pentaborate (MeB5O8), pyroborate (Me2B4O7), and metaborate (MeBO2), wherein Me represents Li, Na, K, Rb, and Cs, preferably one or a combination of two of sodium borate and potassium borate; the alkali metal borate content in the catalyst is 1% to 40% of the total mass of the catalyst; preferably 1.5% to 35%, and more preferably 2% to 30%; the carrier of the catalyst is one or a combination of two or more oxides of CeO2, Al2O3, ZrO2, TiO2, and SiO2.

[0013] A second aspect of the present invention provides a method for preparing a Pt-based water-gas shift reaction catalyst, characterized in that it comprises the following steps:

[0014] The soluble salt of active metal Pt and alkali metal borate are loaded onto the carrier by impregnation method, and dried at 60-120°C for 4-24 hours; the dried product is placed in an air atmosphere and / or an inert atmosphere and the temperature is raised to 300-600°C at a rate of 1-20°C / min, and calcined for 0.5-10 hours to obtain a Pt / alkali metal borate / carrier catalyst.

[0015] The impregnation method includes co-impregnation and step-by-step impregnation. The co-impregnation refers to loading the active metal Pt and the alkali metal borate onto the carrier by impregnation in one step; the step-by-step impregnation refers to loading the active metal Pt and the alkali metal borate onto the carrier in sequence by two-step impregnation, including first impregnating the active metal Pt and then impregnating the alkali metal borate, and first impregnating the alkali metal borate and then impregnating the active metal Pt.

[0016] The soluble salt of Pt is one or more of chloroplatinic acid, platinum chloride, platinum nitrate, tetraamine platinum dichloride, tetraamine platinum nitrate, tetraamine platinum acetate or platinum acetylacetonate.

[0017] The drying temperature is preferably 70-110°C, more preferably 80-100°C; the drying time is preferably 2-20h, more preferably 4-15h; the roasting heating rate is preferably 3-10°C / min, more preferably 5-8°C / min; the roasting temperature is preferably 350-550°C, more preferably 400-500°C; the roasting time is preferably 1-8h, more preferably 2-4h.

[0018] The third aspect of the present invention provides an application of a Pt-based water-gas shift reaction catalyst, which does not require pre-reduction when used in the water-gas shift reaction. The conditions for the water-gas shift reaction are: water and CO are essential components in the reaction gas, and the molar ratio of water to CO is (2.0-12):1, preferably (2.5-10):1, and more preferably (3-8):1; the reaction gas does not contain or contains non-essential components, and the non-essential components are one or more of N2, CO2, H2, Ar, and He, and the molar fraction of the non-essential components in the reaction gas is 0-90%; the space velocity of the reaction raw materials through the catalyst bed is 5000-300000ml·h -1 ·g -1 催化剂 , preferably 10000~250000ml·h -1 ·g -1 催化剂 , more preferably 20000 to 200000 ml·h -1 ·g -1 催化剂 ; The pressure of the reaction system is 0.1 to 4 MPa, preferably 0.1 to 2 MPa, and more preferably 0.1 to 1 MPa; the reaction temperature is 200 to 500°C, preferably 225 to 475°C, and more preferably 250 to 450°C.

[0019] The reaction evaluation device process for verifying the technical solution of the present invention is as follows Figure 1 As shown. The raw gas ① is metered by the flow meter ② and then enters the preheater ⑤. The water ③ is quantitatively transported into the preheater ⑤ through the metering pump ④. The mixed material is preheated to 100-400℃ in the preheater ⑤. The preheated material enters the reactor ⑦ set in the heating area of ​​the reactor ⑥. The constant temperature area of ​​the reactor ⑦ is provided with a catalyst bed ⑧. After the reaction, the material is separated into gas phase products and condensed water through the condenser ⑨. The condensed water is released by the stop valve ⑩ at an appropriate time, and the gas product is discharged through the back pressure valve ⑩. After it drops to normal pressure, it passes through the gas flow meter After metering, empty the pipe. There is a sampling branch on the top to supply the gas chromatograph Sampling and analysis.

[0020] Compared with conventional high temperature shift and low temperature shift catalysts, the present invention has the following advantages:

[0021] (1) The Pt-based water-gas shift reaction catalyst provided by the present invention is prepared by a simple impregnation method, which has the advantages of being simple, mature and highly reproducible.

[0022] (2) The Pt-based water-gas shift reaction catalyst provided by the present invention improves the catalyst's ability to activate water by introducing alkali metal borates, and can inhibit the formation of carbonate species in the catalyst at low temperatures, thereby improving the catalyst's water-gas shift reaction activity and stability.

[0023] (3) The Pt-based water-gas shift reaction catalyst provided by the present invention has the advantages of high activity, high selectivity, long-term operation stability and good start-stop stability.

[0024] (4) The Pt-based water-gas shift reaction catalyst provided by the present invention does not require reduction operation before use and is not afraid of air oxidation. It can adapt to the application environment of rapid startup and repeated start and stop of fuel cell systems, overcoming many limitations of traditional water-gas shift reaction catalysts in non-steady-state operating environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a schematic diagram of the process of the CO water-gas shift reaction catalyst evaluation device;

[0026] ①CO raw gas, ②flow meter, ③water, ④metering pump, ⑤preheater, ⑥reaction furnace, ⑦reactor, ⑧catalyst bed, ⑨condenser, ⑩stop valve, Back pressure valve, Gas flow meter, Gas chromatograph, Vent the line.

[0027] Figure 2 The water-gas shift reaction evaluation data obtained from Examples 1 to 3 and Comparative Examples 1 to 2.

[0028] Figure 3 The water-gas shift reaction evaluation data at different space velocities obtained in Example 4 are shown.

[0029] Figure 4 These are the long-term operation stability evaluation data of the water-gas shift catalysts obtained in Example 5 and Comparative Examples 3-4.

[0030] Figure 5 The start-stop stability evaluation data of the catalysts obtained in Example 6 and Comparative Examples 5 to 6 under a raw gas atmosphere.

[0031] Figure 6 The water-gas shift reaction evaluation data obtained in Examples 11 to 13 and Comparative Example 7.

[0032] Figure 7 The water-gas shift reaction evaluation data obtained in Example 1, Examples 14 to 16, and Comparative Example 1.

[0033] Figure 8The water-gas shift reaction evaluation data obtained from Example 1, Comparative Example 1, and Comparative Examples 8-9. DETAILED DESCRIPTION

[0034] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited to these specific embodiments.

[0035] Example 1

[0036] (1) Catalyst preparation: Weigh 1.0 g of CeO2 carrier, then weigh 0.1327 g of chloroplatinic acid based on the mass content of Pt in the catalyst being 5%, weigh 0.0572 g of sodium metaborate (NaBO2), dissolve them in 1 ml of deionized water to obtain an impregnation solution, then add the impregnation solution to 1.0 g of CeO2 carrier, stir evenly and dry at 80°C for 2 h; place the dried product in an air atmosphere and heat it to 400°C at a rate of 5°C / min, and calcine it for 2 h. The obtained catalyst is recorded as 5Pt / 5.2%wt NaBO2 / CeO2.

[0037] (2) Catalyst evaluation: The obtained 5Pt / 5.2%wt NaBO2 / CeO2 catalyst was tableted and granulated, and then 0.2 g (40-60 mesh) of catalyst particles was placed Figure 1 The water-gas shift reaction was evaluated in the micro fixed-bed reactor shown in FIG. The reaction feed gas composition was 40% H2 / 15% CO / 13% CO2 / 32% Ar, the water to CO molar ratio was 3, and the feed gas flow rate was 230 ml min -1 , converted to the feed mass space velocity (WHSV) of about 100000 ml h -1 ·g -1 催化剂 The reaction pressure was 0.1 MPa, and the reaction temperatures were 200°C, 250°C, 275°C, 300°C, 325°C, 350°C, 400°C, and 500°C, respectively. The reaction was carried out for 30 min at each temperature. The specific results are shown in Figure 2 .

[0038] Embodiment 2:

[0039] The process of Example 1 was repeated, except that 0.043 g of NaBO2 was added during the catalyst preparation process. The catalyst obtained was recorded as 5Pt / 3.9%wt NaBO2 / CeO2. The catalyst evaluation results are shown in Figure 2 .

[0040] Embodiment 3:

[0041] The process of Example 1 was repeated, except that 0.0859 g of NaBO2 was added during the catalyst preparation process. The catalyst obtained was recorded as 5Pt / 7.6%wt NaBO2 / CeO2. The catalyst evaluation results are shown in Figure 2 .

[0042] Embodiment 4:

[0043] The process of Example 1 was repeated, except that the catalyst evaluation temperature was fixed at 400°C, and the reaction mixture feed flow rate was adjusted to be 5000 ml·h-1 and 5000 ml·h-2, respectively. -1 ·g -1 催化剂 、100000ml·h -1 ·g -1 催化剂 、150000ml·h -1 ·g -1 催化剂 、200000ml·h -1 ·g -1 催化剂 、300000ml·h -1 ·g -1 催化剂 The activity of 5Pt / 5.2%wt NaBO2 / CeO2 catalyst at different space velocities at 400℃ was investigated. The specific results are shown in Figure 3 .

[0044] Embodiment 5:

[0045] The process of Example 1 was repeated except that the catalyst evaluation temperature was fixed at 400°C and the space velocity (WHSV) was fixed at 200000 ml·h -1 ·g -1 催化剂 The results of sampling and analysis were taken every hour. The stability of 5Pt / 5.2%wtNaBO2 / CeO2 catalyst was investigated for 50 hours. The specific results are shown in Figure 4 .

[0046] Embodiment 6:

[0047] The process of Example 1 was repeated except that the catalyst evaluation temperature was fixed at 400°C and the space velocity (WHSV) was fixed at 200000 ml·h -1 ·g -1 催化剂After 30 minutes of reaction, the sample was collected and analyzed. Then the reaction was stopped, the catalyst was cooled to room temperature in the raw gas atmosphere, and then heated to 400°C for activity evaluation. This process was repeated 5 times to investigate the start-stop stability of the catalyst in the raw gas atmosphere. The specific results are shown in Figure 5 .

[0048] Embodiment 7:

[0049] The process of Example 1 was repeated, except that the drying temperature during catalyst preparation was 60°C, the drying time was 24h, the catalyst calcination heating rate was 1°C / min, the calcination temperature was 300°C, the calcination time was 10h, and the final catalyst obtained was 5Pt / 5.2%wt NaBO2 / CeO2-300°C-10h. The molar ratio of water to CO during catalyst evaluation was 2:1, and the pressure was 4MPa.

[0050] Embodiment 8:

[0051] The process of Example 1 was repeated, except that the drying temperature during catalyst preparation was 120°C, the drying time was 4h, the catalyst calcination heating rate was 20°C / min, the calcination temperature was 600°C, the calcination time was 0.5h, and the final catalyst obtained was 5Pt / 5.2%wt NaBO2 / CeO2-600°C-0.5h. The molar ratio of water to CO during catalyst evaluation was 12:1, and the pressure was 0.1MPa.

[0052] Embodiment 9:

[0053] The process of Example 1 was repeated, except that the amount of chloroplatinic acid added during the catalyst preparation was 0.0135 g, the amount of NaBO2 added was 0.0102 g, and the final catalyst was recorded as 0.5Pt / 1wt%NaBO2 / CeO2.

[0054] Embodiment 10:

[0055] The process of Example 1 was repeated, except that the amount of chloroplatinic acid added during the catalyst preparation was 0.5310 g, the amount of NaBO2 added was 0.80 g, and the final catalyst was recorded as 10Pt / 40wt%NaBO2 / CeO2.

[0056] Embodiment 11:

[0057] The process of Example 1 was repeated, except that the carrier used in the catalyst preparation process was 20wt% CeO2-Al2O3, the amount of chloroplatinic acid added was 0.0265g, and the amount of NaBO2 added was 0.0337g. The catalyst finally obtained was recorded as 1Pt / 3.2wt%NaBO2 / 20wt%CeO2-Al2O3. The catalyst evaluation results are shown in Figure 6 .

[0058] Embodiment 12:

[0059] The process of Example 11 was repeated, except that the alkali metal borate added during the catalyst preparation process was sodium pyroborate (Na2B4O7), and the amount added was 0.1031 g. The catalyst finally obtained was recorded as 1Pt / 9.3wt%Na2B4O7 / 20wt%CeO2-Al2O3. The catalyst evaluation results are shown in Figure 6 .

[0060] Embodiment 13:

[0061] The process of Example 11 was repeated, except that the alkali metal borate added during the catalyst preparation process was sodium pentaborate (NaB5O8) in an amount of 0.1337 g. The resulting catalyst was recorded as 1Pt / 11.7wt%NaB5O8 / 20wt%CeO2-Al2O3. The catalyst evaluation results are shown in Figure 6 .

[0062] Embodiment 14:

[0063] The process of Example 1 was repeated, except that the carrier used in the catalyst preparation process was 5wt% SiO2-CeO2. The catalyst obtained was recorded as 5Pt / 5.2%wt NaBO2 / 5wt%SiO2-CeO2. The catalyst evaluation results are shown in Figure 7 .

[0064] Embodiment 15:

[0065] The process of Example 1 was repeated, except that the carrier used in the catalyst preparation process was TiO2. The catalyst obtained was recorded as 5Pt / 5.2%wt NaBO2 / TiO2. The catalyst evaluation results are shown in Figure 7 .

[0066] Embodiment 16:

[0067] The process of Example 1 was repeated, except that the carrier used in the catalyst preparation process was 20%wt ZrO2-CeO2. The catalyst obtained was recorded as 5Pt / 5.2%wt NaBO2 / 20%wt ZrO2-CeO2. The catalyst evaluation results are shown in Figure 7 .

[0068] Comparative Example 1

[0069] The process of Example 1 was repeated, except that no alkali metal borate was added during the catalyst preparation process. The final catalyst obtained was 5Pt / CeO2. The catalyst evaluation results are shown in Figure 2 .

[0070] Comparative Example 2

[0071] The process of Example 1 was repeated, except that 0.0739 g of sodium nitrate was added during the catalyst preparation process, and the molar ratio of sodium nitrate to active metal Pt was 10:1. The catalyst finally obtained was recorded as 5Pt / 6.6wt%NaNO3-CeO2. The catalyst evaluation results are shown in Figure 2 .

[0072] Comparative Example 3:

[0073] The process of Comparative Example 1 was repeated, except that the catalyst evaluation temperature was fixed at 400°C and the space velocity (WHSV) was fixed at 200000 ml·h -1 ·g -1 催化剂 The stability of the 5Pt / / CeO2 catalyst was investigated for 50 hours. The specific results are shown in Figure 4 .

[0074] Comparative Example 4:

[0075] The process of Comparative Example 2 was repeated, except that the catalyst evaluation temperature was fixed at 400°C and the space velocity (WHSV) was fixed at 200000 ml·h -1 ·g -1 催化剂 The results of sampling and analysis were performed every 1 hour. The stability of the 5Pt / 6.6wt%NaNO3-CeO2 catalyst was investigated for 50 hours. The specific results are shown in Figure 4 .

[0076] Comparative Example 5:

[0077] The process of Example 1 was repeated except that the catalyst evaluation temperature was fixed at 400°C and the space velocity (WHSV) was fixed at 200000 ml·h -1 ·g-1 催化剂 After 30 minutes of reaction, the sample was collected and analyzed. Then the reaction was stopped, the catalyst was cooled to room temperature in the raw gas atmosphere, and then heated to 400°C for activity evaluation. This process was repeated 5 times to evaluate the start-stop stability of the 5Pt / CeO2 catalyst in the raw gas atmosphere. The specific results are shown in Figure 5 .

[0078] Comparative Example 6:

[0079] The process of Example 1 was repeated except that the catalyst evaluation temperature was fixed at 400°C and the space velocity (WHSV) was fixed at 200000 ml·h -1 ·g -1 催化剂 After 30 minutes of reaction, the sample was collected and analyzed. Then the reaction was stopped, the catalyst was cooled to room temperature in the raw gas atmosphere, and then heated to 400°C for activity evaluation. This process was repeated 5 times to evaluate the start-stop stability of the 5Pt / 6.6wt%NaNO3-CeO2 catalyst in the raw gas atmosphere. The specific results are shown in Figure 5 .

[0080] Comparative Example 7:

[0081] The process of Example 11 was repeated, except that no alkali metal borate was added during the catalyst preparation process. The final catalyst obtained was 1Pt / 20wt% CeO2-Al2O3. The catalyst evaluation results are shown in Figure 6 .

[0082] Comparative Example 8:

[0083] The activity of the Cu / ZnO / Al2O3 industrial low temperature shift catalyst was evaluated according to the catalyst evaluation conditions in Example 1. The results are shown in Figure 8 .

[0084] Comparative Example 9:

[0085] The activity of the Fe3O4-Cr2O3 industrial high temperature shift catalyst was evaluated according to the catalyst evaluation conditions in Example 1. The results are shown in Figure 8 .

[0086] The application test results show that the alkali metal borate modified Pt-based water-gas shift reaction catalyst provided by the present invention has excellent catalytic performance: (1) 5Pt / 5.2wt%NaBO2-CeO2 catalyst in a simulated atmosphere of 40%H2 / 15%CO / 13%CO2 / 32%Ar, with a water to CO molar ratio of 3:1 and a space velocity of 100000ml·h -1 ·g -1 催化剂Under the same conditions, the CO conversion rate at 275°C is close to the equilibrium conversion rate, and the activity is much higher than that of the 5Pt / CeO2 water-gas shift catalyst; (2) The 5Pt / 5.2wt% NaBO2-CeO2 catalyst has good stability. In the simulated atmosphere, the water:CO molar ratio is 3:1, the reaction temperature is 400°C, and the space velocity is 200000ml·h -1 ·g -1 催化剂 Under the above conditions, the CO conversion rate of the catalyst was maintained at above 75% within 50 hours, while the CO conversion rate of the catalyst of 5Pt / 6.6wt%NaNO3-CeO2 decreased by more than 30% within 50 hours; (3) The catalyst of 5Pt / 5.2wt%NaBO2-CeO2 had good stability under the raw gas atmosphere. After 5 start-stop cycles under the raw gas atmosphere, the CO conversion rate remained basically unchanged, while the CO conversion rates of the catalyst of 5Pt / CeO2 and the catalyst of 5Pt / 6.6wt%NaNO3-CeO2 decreased significantly; (4) Figure 8 It can be seen that the activity of 5Pt / 5.2wt%NaBO2-CeO2 is much higher than that of the traditional Fe3O4-Cr2O3 high temperature shift catalyst and Cu / ZnO / Al2O3 low temperature shift catalyst, and is also much higher than that of the traditional Pt / CeO2 catalyst.

[0087] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various changes. Any modification, improvement, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A Pt-based water-gas shift reaction catalyst, characterized in that: The catalyst composition is Pt / alkali metal borate / carrier; the active component of the catalyst is Pt, and the Pt content is 0.5% to 10% of the total mass of the catalyst; the alkali metal borate content in the catalyst is 1% to 40% of the total mass of the catalyst; the carrier of the catalyst is one or a combination of two or more oxides of CeO2, ZrO2, TiO2, and SiO2; The alkali metal borate in the catalyst is selected from one or two of pentaborate MeB5O8, pyroborate Me2B4O7, and metaborate MeBO2, wherein Me represents one of Li, Na, K, Rb, and Cs; The preparation method of the catalyst comprises the following steps: The soluble salt of active metal Pt and alkali metal borate are loaded onto the carrier by impregnation method, and dried at 60-120 °C for 4-24 h; the dried product is placed in an air atmosphere and heated from room temperature to drying temperature to 300-600 °C at a rate of 1-20 °C / min, and calcined for 0.5-10 h to obtain a Pt / alkali metal borate / carrier catalyst; The impregnation method is co-impregnation; the co-impregnation means that the active metal Pt and the alkali metal borate are impregnated into the carrier in one step.

2. The Pt-based water-gas shift reaction catalyst according to claim 1, characterized in that: The content of the active component Pt in the catalyst is 0.8% to 8% of the total mass of the catalyst; the content of the alkali metal borate in the catalyst is 1.5% to 35% of the total mass of the catalyst.

3. The Pt-based water-gas shift reaction catalyst according to claim 1, characterized in that: The content of Pt, an active component of the catalyst, is 1-5wt% of the total mass of the catalyst; and the content of alkali metal borate in the catalyst is 2%-30% of the total mass of the catalyst.

4. The Pt-based water-gas shift reaction catalyst according to claim 1, characterized in that: In the catalyst, Me in the alkali metal borate is one of Na and K.

5. The Pt-based water-gas shift reaction catalyst according to claim 1, characterized in that: The soluble salt of the active metal Pt is one or more of chloroplatinic acid, platinum chloride, platinum nitrate, tetraammineplatinum dichloride, tetraammineplatinum nitrate, tetraammineplatinum acetate or platinum acetylacetonate; The drying temperature is 70-110°C, and the drying time is 2-20 h. The temperature is raised from room temperature to the drying temperature to the roasting temperature at a heating rate of 3-10°C / min. The roasting temperature is 350-550°C, and the roasting time is 1-8 h.

6. The Pt-based water-gas shift reaction catalyst according to claim 1, characterized in that: The drying temperature is 80-100°C; the drying time is 4-15 h; the temperature is raised from room temperature to the drying temperature to the roasting temperature at a heating rate of 5-8°C / min; the roasting temperature is 400-500°C; and the roasting time is 2-4 h.

7. Use of the catalyst according to any one of claims 1 to 6, characterized in that: The catalyst is used for water-gas shift reaction.

8. The use according to claim 7, characterized in that: The water gas shift reaction conditions applicable to the catalyst are as follows: the reaction temperature is 200-500 °C, water and CO are essential components in the reaction gas, and the molar ratio of water to CO is (2-12):1; the reaction gas contains no or no unnecessary components, and the unnecessary components are one or more of N2, CO2, H2, Ar, and He, and the molar fraction of the unnecessary components in the reaction gas is 0-90%; the space velocity of the reaction raw materials passing through the catalyst bed is 5000-300000 ml·h -1 ·g -1 催化剂 ; The pressure of the reaction system is 0.1~4 MPa.

9. The use according to claim 8, characterized in that: The molar ratio of water to CO is (2.5-10):1; the reaction temperature is 225-475°C; the space velocity of the reaction raw materials passing through the catalyst bed is 10000-250000 ml·h -1 ·g -1 催化剂 ; The pressure of the reaction system is 0.1~2 MPa.

10. The use according to claim 8, characterized in that: The molar ratio of water to CO is (3-8):1; the reaction temperature is 250-450°C; the space velocity of the reaction raw materials passing through the catalyst bed is 20000-200000 ml·h -1 ·g -1 催化剂 ; The pressure of the reaction system is 0.1~1 MPa.

11. The use according to any one of claims 8 to 10, characterized in that: The catalyst does not need to be reduced before catalyzing the reaction.

Citation Information

Patent Citations

  • Carbon monoxide water vapor conversion reaction method using Pt-based catalyst

    CN111139108A

  • Preparation method of platinum-supported catalysts for water gas conversion reaction

    CN103586023A

  • Catalyst used for reverse water gas shift reaction as well as preparation and application of catalyst

    CN108144637A